Eastern partnership and expansion: the Ukrainian perspective - Todorova Anna („RIK-U” Kft., 2018)
Abstract. The very establishment of the Eastern Partnership in 2009 implemented the differentiation of the EU approaches towards relations with its Southern and Eastern neighbours, who were previously treated equally within the framework of the European Neighbourhood Policy. From Ukraine’s perspective, this was a step in a right direction given that Eastern neighbours are European countries and may aspire for the EU membership once they met necessary criteria. The Ministry of Foreign Affairs of Ukraine clearly stated that Ukraine’s strategic interest with regard to the Eastern Partnership consists in granting the European perspective to the interested partner states thus transforming the initiative into the connecting link with the EU enlargement policy [6]. The analysts maintain that on the EU side, from the Eastern Partnership’s inception central and northern European countries saw strengthening the sovereignty and democracy of their eastern partners as both a good thing in itself and an important hedge against Russia; for southern and western Europeans, the partnership was at best irrelevant and at worst an irritant as they tried to strengthen relations with Moscow. Russia’s invasion of Ukraine has increased the relevance of the Eastern Partnership, but also the fear of provoking Putin’s anger.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: Ukraine; Eastern Partnership